Single incision multi-trocar hepatic cyst excision with partial splenectomy - Palanivelu Chinnusamy; Jasmeet Singh Ahluwalia; Senthilnathan Palanisamy; Rajan Pidigu Seshiyer (Journal of Minimal Access Surgery, 2013)
Introduction: Surgery has the potential to remove the entire hydatid cyst and can lead to complete cure. Presence of hydatid cysts in multiple abdominal organs imposes special challenges for laparoscopic management. The patient position and port placement for one organ may not be adequate for other and proper exposure in hydatid cyst is of paramount importance to prevent spillage and complete removal of the cyst. Single incision multi-trocar technique has a unique advantage of allowing surgeon to work in different quadrants of abdomen using the same incision and ports. We report in this paper the first Laparo-endoscopic single-site hepatic cyst excision with partial splenectomy for hydatid cyst in liver and spleen using conventional laparoscopic instruments. Patient and Technique: The procedure was performed on a 64 year old female diagnosed to have Hydatid cyst in segment VIII of liver and another cyst in lower pole of spleen a transverse 3 cm incision was made 6 cm above umbilicus and was deepened up to fascia. Two 10mm and one 5mm ports were inserted. Procedure was completed in 160 minutes without any intra-operative complication. There were no post-operative complication and patient was discharged on day 5. Conclusion: Single incision multi-trocar surgery has cosmetic advantage over standard laparoscopic approach. It is even more marked when two procedures are combined in different quadrants of abdomen. As this is a rare combination procedure so it remains to be determined if this technique offers additional advantages of decreased analgesia, decreased hospital stay or cost effectiveness.